Use of textile waste water along with liquid NPK fertilizer for production of wheat on saline sodic soils. Issue 5 (3rd May 2016) - Yaseen, Muhammad; Aziz, Muhammad Zahir; Jafar, Abdul Aleem; Naveed, Muhammad; Saleem, Muhammad
ABSTRACT: A field experiment in collaboration with a private textile industry (Noor Fatima Fabrics Private (Ltd.), Faisalabad) was conducted to evaluate the effect of disposed water from bleaching unit, printing unit and end drain for improving growth and yield of wheat under saline sodic soil. Textile waste water along with canal water (control) was applied with and without liquid NPK fertilizer. The application of liquid NPK fertilizer with end drain waste water increased plant height, spike length, flag leaf length, root length, number of tillers (m −2 ), number of fertile tillers (m −2 ), 1000 grain weight, grain yield, straw yield and biological yield up to 21, 20, 20, 44, 17, 20, 14, 44, 40 and 41%, respectively compared to canal water (control). Similarly, the NPK uptake in grain was increased up to 15, 30 and 28%, respectively by liquid fertilizer treated end drain water as compare to canal water with liquid fertilizer. Moreover, concentration of different heavy metals particularly Cu, Cr, Pb and Cd was decreased in grains by application of waste water along with liquid NPK. The result may imply that waste water application along with liquid-NPK could be a novel approach for improving growth and yield of wheat in saline sodic soils.